Mixed Reality Technology as a Delivery Mechanism for Psychological Intervention in Adolescents With Asthma: A Qualitative Protocol. (29th April 2021) - Sharrad, Kelsey; Kopsaftis, Zoe; Tai, Andrew; Spurrier, Nicola; Smith, Ross; Esterman, Adrian; Gwilt, Ian; Stallman, Helen; Carson-Chahhoud, Kristin
Australia has one of the highest asthma prevalence rates in the world, with this chronic and debilitating condition affecting one in nine people. The health and mental wellbeing of young people with asthma are worse than not only their peers without asthma but also worse than that of people with asthma at other ages. Psychological interventions could be beneficial in treating symptoms of elevated psychological distress in patients with asthma. However, evidence suggests that engagement with mental health services is low in this population. Technology-based solutions that engage youth may overcome barriers to service uptake for both mental health and asthma management. To fast-track the successful translation of evidence-based treatment into practice, interactive, mixed-reality technologies such as augmented reality (AR), virtual reality (VR) and holographic technology may provide a novel, low-cost solution, yet to date, methodological rigor in the evaluation of mixed reality for this purpose is lacking. To evaluate the perceived usability and acceptability of these technologies, mixed reality tools will be developed by the author team to deliver a component of a psychological intervention for treatment of elevated psychological distress among young people with asthma. Qualitative research will be conducted through one-on-one interviews with young people with asthma, parents/caregivers of young people with asthma, and with health professionals, during which participants will have time to interact with the resources. Moderator guides will be used to direct interviews, and will be supplemented with a questionnaire, including Likert-type measures of usability and acceptability to facilitate triangulation of data. Understanding and data obtained through this study will be used to develop version 2.0 mixed reality tools, which will be tested for feasibility in a RCT. Improving access to and uptake of evidence-based treatments for elevated psychological distress in young people with asthma may reduce the burden of this highly prevalent disease.